Detection of Helicobacter pylori IgG and IgM Antibodies in Iraqi Dyspeptic Patients - Muna Turkey Al-Mossawei; Wasan Hatem Rzooqi; Safaa Abdulrazzaq (مجلة مركز بحوث التقنيات الاحيائية, 2016)
This study is conducted to detect H. pylori IgG and IgM antibodies by different serological techniques (Immunochromatography test for rapid H. pylori IgG antibodies detection and enzyme linked immunosorbant assay test for H. pylori IgM antibodies detection). One hundred and twenty five dyspeptic patients are subjected to esophageal gastroduodenoscopy at the Endoscopy Unit at Baghdad Teaching Hospital from 10/1/2013 to 8/1/2014. Venous blood samples are collected from each patient. This study recorded, (89%) sensitivity for each of IgM Test by ELISA kit and Rapid IgG Test by Immunochromatography kit, but Rapid IgG Test has more specificity (85.64%) than IgM Test (80.8%).The higher prevalence 31.2% of H. pylori IgM antibodies observed among age group (21-40) years, whereas the IgM showed a slight rise 2.4% from the (10-20) years age group as acute H. pylori infection, although statistically there is a nonsignificant (P ≥0.05) association between H. pylori IgM antibodies and gender, but the females (32%) were more affected than males (27.2%). Also recorded significant (P ≤0.05) association between chronic H. pylori infection and gender (male 45% and female 55%), and highly significant association of blood groups phenotypes and Rh factor with H. pylori infection recorded by rapid IgG test (P ≤0.01), as the seropositivity of H. pylori according to rapid IgG test was (35, 15, 0 and 50) % for (A, B, AB and O) patients respectively, and (85and 15) % for Rh+ and Rh- patients, respectively.